Out-executing the competition : building and growing a financial services company in any economy - Rothman, Irv. (Hoboken, N.J. : John Wiley & Sons, 2012)
'An inside look at what makes a successful financial services companyIrv Rothman may not have considered a career in the financial services early on, but he ended up in leadership positions at AT&T, Compaq and, for over a decade, Hewlett-Packard. His consistent record of success and insider perspective make him the perfect guide to the art of building and growing a financial services company, and in Out-Executing the Competition he shares his remarkable story and years of experience, giving readers a glimpse into his numerous accomplishments and providing takeaways they can apply to their own companies, whatever the industry.An engaging and lively account of Rothman's career focusing on his work at financial services companies during some of the most economically challenging periods of the past thirty years, the book explores the methods and tactics he used to help his companies not only weather financial uncertainty, but to thrive. Tells the story of financial services company expert Irv Rothman, in his own words Includes invaluable insights into how to build a financial services company that can survive and thrive in even the toughest economic climate Helps readers working at financial services companies and in other industries to construct solid businesses that can outperform their competition Part biography, part how-to guide, Out-Executing the Competition is the ultimate inside look at building a financial services company that's sure to succeed'--
Includes index.
Keywords: Rothman, Irv; Investment advisors -- United States -- Biography; Stockbrokers -- United States -- Biography; Finance -- United States; Investments -- United States